Law enforcement against online fraud on e-commerce platforms based on law no. 19 of 2016 - Sofiyana, Nurani; Prastyanti, Rina Arum (Institute Of computer Science (IOCS), 2025)
The rapid spread of information and communication technology, particularly e-commerce, has changed the way economies transact around the world, expand markets, and make it easier. However, along with these advances, a new problem has arisen in the form of increasing cases of online fraud that are detrimental to consumers. Online fraud, especially those that occur on e-commerce platforms, is one of the main problems that threatens consumer trust in companies (Hartanto, 2016). This qualitative study was carried out with normative juridical methods. This method looks at laws and regulations, case studies, and academic research. The study found different types of online fraud, ranging from sending goods that don't fit the description or counterfeit goods to using the wrong payment system. Despite the fact that the ITE Law provides a strong legal basis for cracking down on fraudsters, there are several challenges in implementing it (ZAHRA, 2025). These include constraints with digital forensic human resources and difficulties in identifying and tracking perpetrators. Additionally, the lack of digital literacy makes the situation worse because consumers are more vulnerable to fraud. As a result, this study suggests increasing the technical capacity of law enforcement officials, cross-sector collaboration between the government and the public, and better digital literacy programs to create a safe, fair, and trustworthy e-commerce ecosystem (Andreaningrum et al., 2024).